CONSTRUCTION OF A WATER STORAGE TUB FOR ABLUTION AT THE MUHAJIRIN MOSQUE IN BANDA ACEH - Azzahra, Fatimah; Rani, Hafnidar A; Murdani, Murdani; Maryadin, Maryadin; Aripinsyah, Aripinsyah (Universitas Muhammadiyah Aceh, 2022)
The proper ablution place becomes one of mosque facilities to be concerned by the community and completed by the water used for ablution activity. The water used in Muhajirin Mosque is sourced from Tirta Daroy Regional Drinking Water Company (PDAM), but the supply is less smooth impacting the water used for ablution activity during the praying times is insufficient. It is required to build water storage with the dimension 3 m x 1.5 m x 1.2 m. The water storage is utilized to fill the water when the PDAM water supply is smooth to solve the water deficit for ablution. The implementation of this community dedication activity consists of survey and observation, drawing designing, discussion, building construction and hand over activity. The output of this activity is providing supporting building used for ablution activity to the community surrounding Muhajirin Mosque in Punge Blang Cut Village, Jaya Baru Sub District, Banda Aceh City. This building is useful for the ablution water need in the praying times and other significant benefits for community. The follow up of this activity is expected to be built a water reservoir as the water reserve to save the electricity and to ensure that the water will be supply if the electricity is off.Keyword: Build water storage, ablution place, mosque